Gender, religion and nation in global interactions: Motherhood in Sri Lanka , Israel and Nigeria Geschlecht, Religion und Nation in globalen Verflechtungen: Mutterschaft in Sri Lanka, Israel und Nigeria - Albrecht, Jessica; Bachmann, Judith; Kirchner, Anna (Zeitschrift für Religionswissenschaft, 2024)
The approaches of a global history of religion have made a decisive contribution to the understanding of general concepts such as religion as historically evolved and changeable. They have also shown that the understanding of religion is shaped by its relation with other general concepts such as nation. Gender has hardly been considered in these studies. However, there are interactions between gender, nation, and religion, which we would like to demonstrate in this article using a comparative approach of motherhood. Drawing on case studies from Sri Lanka, Israel and Nigeria, we explain how the comparative element of motherhood functions in different contexts, how identities are constructed, how this affects religion, nation and gender, and how motherhood serves as a mechanism through which oppression operates and in which agency is possible.
Created from Fastlane, Scopus look-up
Keywords: ethnicity; Gender; Motherhood; Nationalism; Religion